Patient satisfaction and treatment adherence for urban adolescents and young adults with pelvic inflammatory disease. Issue 1 (2018) - Anders, Jennifer; Chung, Alexandra Hill Shang-En; Butz, Arlene; Rothman, Richard; Gaydos, Charlotte; Perin, Jamie; Trent, Maria
No abstract available